A rare case of diploic venous anomaly: asymptomatic venous sac expanding in the diploe - Iwamuro, Hirokazu (Springerplus, 2016)
BACKGROUND: Vascular anomalies accompanied with the diploic veins are rare. Among them, sinus pericranii, which is characterized by abnormal connections between intra- and extracranial venous systems, is relatively common. Besides sinus pericranii, a few cases of subepicranial varix with connections to diploic veins have been reported, but these varices had no connections to intracranial venous sinuses. Herein, we present a rare case of an expanding venous sac in the diploe which communicated with the intracranial sinus but not with the extracranial venous systems. CASE PRESENTATION: An adult woman presented to us with a minor transient headache. Although no abnormal appearances were found on her scalp, imaging studies showed a club-shaped venous sac in the left parietal diploe that communicated with the superior sagittal sinus and diploic veins on the medial and lateral sides, respectively. It was revealed that the lesion had expanded as compared with a previous computed tomography image. Surgery was performed to intercept venous supply from the diploic veins, and the lesion was filled with thrombi. In a follow-up of 15 months, there was no recurrence of abnormal venous flow. Histological examination showed the endothelial lining in the membranous wall of the sac, which is typically observed in sinus pericranii. However, no communication with the pericranial veins of the scalp was identified on the imaging studies and intraoperative observation. Accordingly, it was diagnosed as another entity “intradiploic varix”. CONCLUSIONS: The abnormal connection between the intracranial and the diploic venous systems via the large venous sac was surgically treated. It was pathologically similar to sinus pericranii, but anatomically considered to be another form of venous anomaly. In cases of expanding lesions, surgical treatment is recommended.